2014
DOI: 10.1128/aac.02307-13
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Supplementation Increases Rifampin Exposure among Tuberculosis Patients Coinfected with HIV

Abstract: f Nutritional supplementation to tuberculosis (TB) patients has been associated with increased weight and reduced mortality, but its effect on the pharmacokinetics of first-line anti-TB drugs is unknown. 2 ) were randomized to receive nutritional supplementation during the intensive phase of TB treatment. Rifampin plasma concentrations were determined after 1 week and 2 months of treatment. The effects of nutritional supplementation, HIV, time on treatment, body weight, and SLCO1B1 rs4149032 genotype were exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
85
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 59 publications
(90 citation statements)
references
References 30 publications
4
85
0
1
Order By: Relevance
“…Praygod 2011b TZA included only HIV-positive patients and although the trend was towards a benefit this did not reach statistical significance. Jeremiah 2014 TZA noted a greater increase in mean weight gain in the supplemented group compared to the non-supplemented group after 8 weeks; however the difference was not appreciable (1.09 kg, P < 0.6, authors' own figures). The 3 other trials all demonstrated clinically important benefits.…”
Section: Summary Of Findings For the Main Comparisonmentioning
confidence: 81%
See 4 more Smart Citations
“…Praygod 2011b TZA included only HIV-positive patients and although the trend was towards a benefit this did not reach statistical significance. Jeremiah 2014 TZA noted a greater increase in mean weight gain in the supplemented group compared to the non-supplemented group after 8 weeks; however the difference was not appreciable (1.09 kg, P < 0.6, authors' own figures). The 3 other trials all demonstrated clinically important benefits.…”
Section: Summary Of Findings For the Main Comparisonmentioning
confidence: 81%
“…Eleven trials specifically included people with HIV, and presented some results separately for HIV positive and HIV negative participants (Schön 2003 ETH; Range 2005 TZA; Semba 2007 MWI; Villamor 2008 TZA; Wejse 2008 GNB; Lawson 2010 NGA; Mehta 2011 TZA; Sudarsanam 2010 IND; Schön 2011 ETH; Ralph 2013 IDN; Jeremiah 2014 TZA). Four of the trials that presented results for HIV-positive and HIV-negative participants separately used stratified randomization (Villamor 2008 TZA; Wejse 2008 GNB; Sudarsanam 2010 IND; Jeremiah 2014 TZA), but six tested participants for HIV following randomization (Schön 2003 ETH; Range 2005 TZA; Semba 2007 MWI; Lawson 2010 NGA; Mehta 2011 TZA; Schön 2011 ETH), and therefore the subgroup analyses by HIV status cannot be said to be truly randomized.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations